Reflections of material and cultural vocabulary associated with the horse in lyric-epic works - Amangeldy А.А.; Tleuzhan Д.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
In the Kazakh language the most fruitfully developed professional vocabulary relating to the four types of domestic animals, and especially the words characterizing the horse. In the Kazakh folklore, namely in the lyric-epic works language facts applied to the horse are leryetten found. This article presents the linguistic facts related to horse breeding in the lyric-epic work of the Kozy Korpesh – Bayan Sulu and provides a comprehensive analysis of the vocabulary of material culture in the word-formation, ethnolinguistic and linguistic-cultural aspect. Also in the article the authors conducted a detailed word-formation, etymological analysis of the words relating to horse breeding, which are found in the poem. The names of products derived from horses are analyzed comprehensively. Ethnolexis in the epic associated with the horse, horse breeding was studied by certain lexico-grammatical groups